Picard: a mal aimé among regional languages?. Issue 2 (July 2019) - Hornsby, David
ABSTRACT: Although often seen as a medieval rival to French, Picard has received far less official recognition and support than more celebrated regional languages such as Breton or Occitan. A shared history and high degree of linguistic similarity with the national language appear to have engendered a perception that it is simply 'bad French', but for supporters such Eloy (1997 ) Picard remains potentiellement une vraie langue, worthy and in need of status enhancement initiatives enjoyed by other regional languages. Promotion of language status for Picard, however, is found to be fraught with practical difficulties, not least of which are a lack of territorial unity and major cultural differences between the north and south of the picardophone area. Equally importantly, the discourse of languagehood fosters notions of linguistic purity which ignore the extensive mixing of local, supralocal and national elements that has always been evident in Picard writing and speech. This in turn engenders linguistic insecurity, notably among urban working-class speakers, whose speech can all too easily be caricatured as both 'bad French' and 'bad patois', with obvious consequences for intergenerational transmission. The well-intentioned promotion of Picard as a regional language may therefore, perversely, be detrimental to the very varieties it serves.